The sacraments of the law and the law of the sacraments - Hahn, Judith (Cambridge University Press, 2023)
In this book, 'sacramentality' is proposed as a category that encompasses the performative power of religious and legal rituals. Law uses sacramental action to change reality through performative acts, while religion uses law to organise religious ritual. Thus, law and religion intertwine to produce legal, spiritual, and other social effects.